Transformasi Desain Pembelajaran Pasca Pandemi Covid-19 berbasis pembelajaran Digital Kurikulum 2013: Studi Kasus Sekolah Dasar Multikultural - Suryaman Suryaman; Bella Cornelia Tjiptady; Triman Juniarso (Elementary Teacher Education Program, Majalengka University, 2023)
All levels of education must transform to adapt through digital learning. Elementary schools become educational institutions that develop curricula and educational processes to build and develop a new culture towards a multicultural society. Multicultural education has now been integrated with the subject matter contained in the 2013 curriculum. The purpose of this research is to explore post-covid-19 pandemic learning designs based on digital learning in the 2013 curriculum. The research method used is a qualitative case study. The results showed that the implementation of multiculturalism education during the Covid-19 pandemic was carried out with four activity programs, namely: 1) entrepreneurial leadership programs, 2) content-oriented programs, 3) student-oriented programs, and 4) social-oriented programs.